Representasi Krisis Ekologis dalam Cerita Rakyat Genting dan Gentas: Kajian Ekokritik Sastra Lawrence Buell: The Representation of the Ecological Crisis in the Folktales of Genting and Gentas: An Ecocritical Study of Literature by Lawrence Buell - Lavenia, Ryca Anggun; Ulwatunnisa, Marwah (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2026)
The application of literary ecocriticism in analyzing folklore is important to develop. Folklore depicts greed, environmental destruction, and the loss of ecosystem balance caused by human actions. Genting and Gentas are works of local literature from East Kalimantan that show ecological imbalances in a country, such as drought, which have an impact on the lives of its people. This study aims to provide an overview of the environmental issues in the stories of Genting and Gentas, as well as to describe the environmental ethics principles contained therein. This study uses Lawrence Buell's literary ecocriticism approach and a literature study that focuses on reference materials. The results of the study show that the presence of ecological disasters in the form of long droughts is caused by human negligence in decision-making and extravagant habits that undermine the legitimacy of nature as the basis of life, represented by the community's violation of environmental ethics principles. This research can be used as local teaching material on environmental awareness, as well as a reminder of the spiritual relationship between humans and nature. Applying environmental ethics from the ground up has a positive impact on sustainable living.